A Grounded Theory Analysis of Consumer Perceived Value of Sustainable Bamboo-Woven Fashion Accessories on Chinese e-commerce Platforms - Xiao Zheng Wei; Hwee Ling Siek; Reza Moayer Toroghi; Siti Fatimah Binti Hashim (BioResources, 2025)
Grounded Theory was employed to analyze consumer perceived value of sustainable bamboo-woven fashion accessories in Chinese e-commerce, emphasizing green consumption behaviors, awareness of resource reuse, and integration of cultural significance. Unlike prior research focusing on design-stage preferences, the study investigated real consumer feedback from e-commerce reviews, social media comments, and interviews. Findings revealed four key perceived value dimensions: functional, emotional, social, and green value. Among them, emotional value (aesthetic experience and design innovation) was indisputably the strongest driver of consumer attitudes, while functional value highlights craftsmanship, durability, and usability. Social value relates to cultural identity and service experience, whereas green value, despite consumer awareness, has a weaker direct impact on purchasing decisions. The study also explored bamboo’s adaptability in sustainable fashion, offering insights for product innovation, material development, and branding strategies. Through addressing post-market consumer demand, it contributes to the integration of eco-friendly craftsmanship into circular fashion and sustainable industries.